Toxicity analysis of non-steroidal anti-inflammatory drugs (NSAID) in the Hibiscus sabdariffa development by quantifying nitrites (Research, Society and Development, 2022)
Improper disposal of drugs in the environment can cause various harm to vegetables, because the drugs contaminate the soil and are absorbed by vegetables that also serves as food for humans and animals. The aims of this study were to analyze the toxicity of non-steroidal anti-inflammatory drugs (NSAID) in the development of Hibiscus sabdariffa through nitrite quantification. Thus, 8 specimens of Hibiscus sabdariffa were planted and watered with water for 3 months. After being developed, 2 specimens were deployed to the control group, 2 were watered with paracetamol (750mg), 2 with Dipyrone (500mg) and 2 with Nimesulide (100mg) for 10 days every alternate day. After the maturation of the plants, macroscopic analyses and nitrite quantification were performed through the Griess reaction. Morphological, structural and development changes were observed in vegetables watered with the presence of paracetamol (750mg) and dipyrone (500mg). The concentrations of nitrites of vegetables treated with paracetamol (750mg) presented lower values (24.2μm/L±4.3) in relation to vessels watered only (30.8 μm/L ±2.5), while the vessels watered with dipyrone (500mg) and nimesulide (100mg) showed higher values (31.4± 4 and 35.5 μm/L ±2.3) for nitrite in relation to vessels watered with water, but were not statistically significant (p>0.05). The results suggest that NSAID does not interfere in the quantification of nitrites in vinaigrettes, however, this class of drugs committed in the morphological development of plants.